2013
DOI: 10.1111/head.12158
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunctions in Migraine With and Without Aura: What Is the Role of White Matter Lesions?

Abstract: On the basis of our results, white matter lesions load on magnetic resonance imaging do not seem to contribute to neuropsychological performances deficit in migraineurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 28 publications
6
40
2
Order By: Relevance
“…Our RS‐fMRI findings were not influenced by the WMH load which was suggested, in a previous study, to underlie the executive impairment in patients with MwoA . However, in line with our data, a recent study has failed to demonstrate the causal association between WMH load and cognitive dysfunction in both patients with MwoA and MwA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our RS‐fMRI findings were not influenced by the WMH load which was suggested, in a previous study, to underlie the executive impairment in patients with MwoA . However, in line with our data, a recent study has failed to demonstrate the causal association between WMH load and cognitive dysfunction in both patients with MwoA and MwA.…”
Section: Discussionsupporting
confidence: 85%
“…This executive dysfunction seems to be most prominent during attacks, but there is converging evidence that the processing and perception of stimuli is abnormal also during the interictal period . The relationship between described cognitive deficits and cerebral structural and functional abnormalities in patients with migraine is still under debate . In the last years, the development of resting‐state functional magnetic resonance imaging (RS‐fMRI) has advanced the assessment of brain functional connectivity .…”
mentioning
confidence: 99%
“…Neuropsychological studies suggests that migraine affect also cognitive functions during attacks and interictal periods [5], even though it is unclear the association between cognitive dysfunctions and migraine. Migraineurs could present executive dysfunction which presumably reflects frontal lobe abnormalities [6], or alteration in memory areas. However, while several authors reported significant lower performances in migraine patients, others did not confirm these findings.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the selected 32 studies are focused on testing the diagnostic congruence of the clinical and neuroanatomical aspects of the FAB, of which 17 studies were aimed at identifying the brain regions or the neural substrates involved in EFs measured by the FAB (Matsui et al, 2006;Guedj et al, 2008;Yoshida et al, 2009;Gordon et al, 2010;Kume et al, 2011;Nagata et al, 2011;Oshima et al, 2012;Chapados and Petrides, 2013;Frota et al, 2013;Kopp et al, 2013;Le Pira et al, 2014;Nakamura-Palacios et al, 2014;Brugger et al, 2015;Lee et al, 2015;Pellechia et al, 2015;Piatella et al, 2015;Khoo et al, 2016), and 15 studies at verifying that the FAB was an appropiate tool for the differential diagnosis in neurological diseases (Slachevsky et al, 2004;Lipton et al, 2005;Paviour et al, 2005;Castiglioni et al, 2006;Oguro et al, 2006;Fukui et al, 2009;Mendez et al, 2009;Woodward et al, 2010;Yamao et al, 2011;Boban et al, 2012;Biundo et al, 2013;Kawai et al, 2013;Krudop et al, 2015;Sitek et al, 2015;Stamelou et al, 2015). Table 1 displays the main characteristics and results from the neuroimaging studies.…”
Section: Resultsmentioning
confidence: 99%
“…by problems with cognitive functioning, commonly called dementias, such as Alzheimer's disease (AD) (Yoshida et al, 2009;Nagata et al, 2011;Oshima et al, 2012;Lee et al, 2015), several types of frontotemporal dementia (FTD) (Guedj et al, 2008;Yoshida et al, 2009;Gordon et al, 2010), or certain condictions such as mild cognitive impairment (MCI) (Yoshida et al, 2009;Kume et al, 2011). The remaining studies include participants affected by frontal lesions (Chapados and Petrides, 2013), stroke (Kopp et al, 2013), migraine (Le Pira et al, 2014), alcohol dependence (Nakamura-Palacios et al, 2014), and idiopathic normal pressure hydrocephalus (Khoo et al, 2016).…”
Section: Brain Regions or Neural Substrates Related To The Fab Performentioning
confidence: 99%